Journal Amy Zoe Mason - Atkinson, Kristine (Simon & Schuster, 2006)
A series of clues and revelations documenting an artist's mysterious fate, presented in collage-style newspaper clippings, e-mails, and private writings, invites readers to search its pages for visual and verbal clues.